Supraclavicular Brachial Plexus Block: Comparison of Varying Doses of Dexmedetomidine with Ropivacaine - Shakya, S.; Singh, J.; Ghimire, A.; Shrestha, B. (Kathmandu University Medical Journal, 2021)
Background Alpha-2 adrenergic receptor agonists have been the focus of interest nowadays as an adjuvant to local anesthesia due to its excellent sedative, analgesic, antihypertensive, anesthetic sparing and hemodynamic stabilizing properties. The ideal dose of dexmedetomidine for brachial plexus block is matter of debate. Objective To find the appropriate minimal dose of dexmedetomidine with desired clinical effects and minimal side-effects, we compared different doses (25 mcg, 50 mcg, 75 mcg and 100 mcg) of dexmedetomidine as an adjuvant to ropivacaine. Method One hundred fifty patients of ASA I and II, aged (18-60) years, weighing (50-60) kilograms undergoing upper limb surgeries under brachial plexus block were enrolled in this prospective, double blind, randomized control study. Patients in all group received 19 ml of 0.5% ropivacaine in common. In addition; group RD25, RD50, RD75 and RD100 received 25 mcg, 50 mcg, 75 mcg and 100 mcg of dexmedetomidine diluted in 1 ml of normal saline (NS) respectively whereas group RD00 received only 1 ml of NS. The duration of analgesia was the primary outcome whereas block characteristics, hemodynamic parameters, oxygen saturation, sedation score and adverse effects were taken as secondary outcome. Statistical analysis was done using ANOVA test, Chi-square test and Scheffe’s multiple comparison tests. Result The demographic profile and baseline hemodynamic variables were comparable in all five groups. Increasing dose of dexmedetomidine showed significant improvement in block characteristics but associated with increase in sedation and incidence of bradycardia. Conclusion We conclude that dexmedetomidine 50 mcg would be an appropriate dose as adjuvant to local anesthesia in brachial plexus block.